Application of Value Added Tax Calculation on Sales: Case Study of PT. Tiga Nova Sentosa - Dian Savitri; Roni Ilham Subagja; Dadi Rosadi; Adi Raharjo; Adjat Sudrajat (Informatics Management, Engineering and Information System Journal, 2023)
This research is entitled an application that can calculate input VAT and output VAT on sales in a company. The lack of utilization of current technology or the system in calculating VAT sometimes results in errors in the difference in payments for the VAT. Therefore, it is necessary to have a system that functions as a VAT calculation tool. So that when the SPT period is reported there are no errors. This application aims to improve accuracy, speed and accuracy so as to reduce errors in management and report generation. The method of data collection uses interviews, observations and literature studies, while the research method used is descriptive method and for its development is Laravel which is an open source PHP-based web application, using the Model-View-Controller concept. This web- based information system was developed using the PHP and MySQL programming languages. The new system can maximize the work of the finance department in tax calculations in a way to be more effective and efficient.